Simulation of Temperature Distribution under Periodic Heating for Analysis of Thermal Diffusivity in Nanometer-Scale Thermoelectric Materials - Yamashita, Naomi; Ota, Yuya; Salleh, Faiz; Navaneethan, Mani; Shimomura, Masaru; Murakami, Kenji; Ikeda, Hiroya (Institute of Electronics, Information and Communication Engineers, 2018)
With the aim of characterizing the thermal conductivity for nanometer-scale thermoelectric materials, we have constructed a new measurement system based on ac calorimetry. Analysis of the obtained data requires time-evolution of temperature distribution in nanometerscale material under periodic heating. In this study, we made a simulation using a C#-program for time-dependent temperature distribution, based on 2-dimensional heat-diffusion equation inclu1ding the influence of heat emission from material edges. The simulation was applied to AlN with millimeter-scale dimensions for confirming the validity and accuracy. The simulated thermal diffusivity for 10×75-mm2-area AlN was 1.3×10-4 m2/s, which was larger than the value set in the heat-diffusion equation. This overestimation was also observed in the experiment. Therefore, our simulation can reproduce the unsteady heat conduction and be used for analyzing the ac calorimetry experiment.